2020
DOI: 10.1007/s40615-020-00712-y
|View full text |Cite
|
Sign up to set email alerts
|

Twitter-Characterized Sentiment Towards Racial/Ethnic Minorities and Cardiovascular Disease (CVD) Outcomes

Abstract: Sentiments towards racial/ethnic racial/ethnic minorities may impact cardiovascular disease (CVD) through direct and indirect pathways. In this study, we assessed the association between Twitter-derived sentiments towards racial/ethnic minorities at state level and individual level CVDrelated outcomes from the 2017 Behavioral Risk Factor Surveillance System (BRFSS). Outcomes included hypertension, diabetes, obesity, stroke, myocardial infarction (MI), coronary heart disease (CHD), and any CVD from BRFSS 2017 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…A rise in negative racial attitudes and racial bias can have significant social, economic, and mental and physical health impacts [ 6 , 7 , 8 ]. Prior research has shown that community-level racial climate is related to birth outcomes [ 9 , 10 , 11 ], cardiovascular outcomes [ 12 ], and mortality [ 13 ] of the area. Such attitudes reflect cultural racism, defined as the infusion of the ideology of racial inferiority in the values, language, imagery, symbols, and unstated assumptions of the larger society [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rise in negative racial attitudes and racial bias can have significant social, economic, and mental and physical health impacts [ 6 , 7 , 8 ]. Prior research has shown that community-level racial climate is related to birth outcomes [ 9 , 10 , 11 ], cardiovascular outcomes [ 12 ], and mortality [ 13 ] of the area. Such attitudes reflect cultural racism, defined as the infusion of the ideology of racial inferiority in the values, language, imagery, symbols, and unstated assumptions of the larger society [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, chronic contextual stress (stress resulting from the socio-political climate and inequitable social structure) [ 54 ] may be more salient in counties with more racial bias. Indeed, previous work has linked community-level racial bias with stress-related outcomes among racially minoritized groups, including cardiovascular risk factors and adverse birth outcomes [ 25 , 27 , 29 ]. Future research should examine these potential mediating pathways linking area-level bias to COVID-19 and other adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Area-level bias may reflect norms and attitudes in a community or may represent a distinct community-level construct and has been shown to predict various domains of population health and health inequities [ 19 , 22 , 23 ]. For example, states with higher anti-Black bias spend less on disabled Medicaid enrollees [ 24 ], and various area-level measures of racial bias have been linked with overall rates of, and racial inequities in: adverse birth outcomes [ 25 ], police killings [ 26 ], cardiovascular risk factors [ 27 ], overall mortality [ 28 ], and mortality related to circulatory disease [ 29 , 30 ]. Proposed pathways linking area-level racial bias to health include institutional discrimination [ 29 ], disrupted social capital and community cohesion [ 28 ], and increased psychosocial stress [ 23 ], which can undermine health for both racially minoritized and White groups [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on prior research, our measure offers new, cost-efficient data sources for characterizing area-level racial sentiment ( Nguyen et al, 2019 ). The measure demonstrated associations with adverse birth outcomes (T. Nguyen et al, 2020 ; Nguyen et al, 2018 ) and cardiovascular outcomes ( Huang, Huang, Adams, Nguyen, & Nguyen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%